18F-Flourodeoxy glucose PET–computed tomography in testicular carcinoma: diagnostic and prognostic value. Issue 12 (December 2019) - Soydal, Cigdem; Araz, Mine; Urun, Yuksel; Gulpinar, Basak; Nak, Demet; Ozkan, Elgin; Kucuk, Nuriye Ozlem
Abstract : Aim: This study aims to assess the diagnostic role of 18 F-FDG PET/computed tomography in primary staging and restaging of testicular cancer in comparison with contrast-enhanced diagnostic thoracic-abdominopelvic computed tomography. Material and method: Thirty-two consecutive male patients with testicular carcinoma (median age: 29, min–max: 17–65) who were referred to the nuclear medicine department for 18 F-FDG PET/computed tomography were retrospectively included in the study. Patients were evaluated based on the 18 F-FDG PET/computed tomography indications and germ cell tumor subtypes. Results: On patient-based analysis, overall sensitivity, specificity, PPV, NPV and accuracy of 18F-FDG PET/computed tomography were 71%, 100%, 100%, 30% and 75%. On lesion-based analysis, for evaluation of lymph node metastasis they were 76%, 100%, 100%, 57% and 81%, and for detection of distant metastasis 85%, 100%, 100%, 90% and 93%, respectively. Median SUVmax for seminomas were calculated as 14.2 and for nonseminomas 7.8 ( P = 0.62) Mean time to progression and overall survival were calculated as 76.6 ± 10.7 and 111 ± 7.5 months, respectively. Mean overall survival and time to progression for PET-positive and negative groups was not found significant ( P = 0.69 and P = 0.81). The only significant factor in predict overall survival was the presence of distant organ metastases in PET/computed tomography (124.6 ± 5.2 vs. 78.7 ± 14.0 months, P = 0.02). Conclusion: In this single-center experience with a limited number of patients, 18 F-FDG PET/computed tomography appears to have a value of staging and restaging for both seminomatous and non-seminomatous GCTs.